Principles of transistor circuits : introduction to the design of amplifiers, receivers, and digital circuits - Amos, S. W. (Stanley William) (Newnes, 2000)
Over the last 40 years, Principles of Transistor Circuits has provided students and practitioners with a text they can rely on to keep them at the forefront of transistor circuit design. Although integrated circuits have widespread application, the role of discrete transistors both as important building blocks which students must understand, and as practical solutions to design problems, remains undiminished. The ninth edition has been thoroughly updated to cover the latest technology and applications, including computer circuit simulation, and many diagrams have been revised to bring them in l.